Salpingectomy vs Tubal Ligation for Sterilization: A Systematic Review and Meta-analysis. Issue 2 (February 2021) - Mills, Kerry; Marchand, Greg; Sainz, Katelyn; Azadi, Ali; Ware, Kelly; Vallejo, Janelle; Anderson, Sienna; King, Alexa; Osborn, Asya; Ruther, Stacy; Brazil, Giovanna; Cieminski, Kaitlynne; et al.
Abstract : (Abstracted from Am J Obstet Gynecol 2020; doi: 10.1016/j.ajog.2020.09.011) The association between removal of the fallopian tubes and decreased risk of ovarian cancer is well documented. Although complete removal of the fallopian tubes (salpingectomy) for the prevention of ovarian cancer seems promising, no unequivocal evidence supports this practice in women seeking sterilization.